2018
DOI: 10.1038/modpathol.2017.166
|View full text |Cite
|
Sign up to set email alerts
|

The Genomics of Prostate Cancer: emerging understanding with technologic advances

Abstract: With the advent of next-generation sequencing technologies and large whole-exome and genome studies in prostate and other cancers, our understanding of the landscape of genomic alterations has dramatically been refined. In additional to well-known alterations in genomic regions involving 8p, 8q, 10q23, common ETS translocations and androgen receptor amplifications, newer technology have uncovered recurrent mutations in SPOP, FOXA1, MED12, IDH and complex large scale genomic alterations (eg, chromoplexy). This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 139 publications
(180 reference statements)
2
37
0
1
Order By: Relevance
“…Although the MIPOL1 loci (the adjacent coding gene) is often described as the insertion point for these ETV1 translocations, the 38 kb region between MIPOL1 and FOXA1 harbors the non-coding gene AL121790.1 (also known as ENSG00000258414 and EST14 ) that has been reported to exhibit androgen-regulated and prostate-specific expression 22 . Fusion of AL121790.1 with ETV1 is consistent with other ETS rearrangements in prostate cancer, which typically involve an AR driven promoter 1 . Analysis of RNA sequencing data from 33 cancer types revealed that AL121790.1 expression is strongly correlated with FOXA1 expression (Spearman correlation = 0.84) (Fig.…”
Section: Resultssupporting
confidence: 73%
See 1 more Smart Citation
“…Although the MIPOL1 loci (the adjacent coding gene) is often described as the insertion point for these ETV1 translocations, the 38 kb region between MIPOL1 and FOXA1 harbors the non-coding gene AL121790.1 (also known as ENSG00000258414 and EST14 ) that has been reported to exhibit androgen-regulated and prostate-specific expression 22 . Fusion of AL121790.1 with ETV1 is consistent with other ETS rearrangements in prostate cancer, which typically involve an AR driven promoter 1 . Analysis of RNA sequencing data from 33 cancer types revealed that AL121790.1 expression is strongly correlated with FOXA1 expression (Spearman correlation = 0.84) (Fig.…”
Section: Resultssupporting
confidence: 73%
“…Prostate cancer is the second leading cause of cancer-related death in men, and has a well-described somatic coding genome defined by distinct molecular subclasses and high heterogeneity 1 . The mutation rate of prostate cancer is relatively low (0.9 and 4.4 mutations per Mb in primary and metastatic disease, respectively) 2,3 and is characterized by an age-related CG>TG mutational signature 4 .…”
Section: Introductionmentioning
confidence: 99%
“…While biopsy-based RNA expression signatures have shown clinical utility in several cancers, understanding the biology of all clinically important foci, within a given organ, can be challenging when the multiplicity as well as the histologic and genomic diversity of cancer foci is high. Prostate cancer is heterogeneous and is multifocal, with multiple, genomically independent tumors identified in up to 80% of men undergoing radical prostatectomy for clinically localized disease (12)(13)(14)(15). Hence, there has been enormous interest in identifying prostate cancer prognostic biomarkers that are unaffected by tissue sampling bias.…”
Section: Introductionmentioning
confidence: 99%
“…Genome sequencing studies in PCa have revealed many recurrent DNA alterations leading to deregulated biological processes involved in prostate development, cell-cycle regulation, androgen signaling, and chromatin organization, among others [ 15 , 16 , 17 ]. From these data, it has also been established that PCa is a cancer entity with a relatively low mutational burden of approximately 1 mutation per megabase [ 18 ].…”
Section: The Genomic Landscape Of Primary Prostate Cancermentioning
confidence: 99%